Effect of Profit Management and Earning per Share on Company Value with Company Size as a Moderation Variable - Fajri, Ahmad Maulana; Yunita, Irma; Mulyana, Emul (Institut Bisnis dan Teknologi Pelita Indonesia, 2023)
This study aims to determine the effect of earnings management and earning per share on firm value and to find out whether firm size is able to moderate the relationship between earnings management and earning per share on company value in food and beverage companies listed on the Indonesia Stock Exchange for the 2018-2022 period. The methodology used in this research is quantitative with a causal associative approach with a sample of food and beverage companies listed on the Indonesian Stock Exchange using a sampling technique. Purposive sampling from 84 populations obtained a sample of 15 companies. The analysis used in this study uses test Moderated Regression Analysis (MRA). The results in this study are that earnings management does not have a significant effect on firm value due to earnings management practices by selecting accounting policies by management which are subjective, then the quality of earnings in the financial statements presented will be low and inaccurate and this can lead to high levels of public trust will decrease so that potentially many investors will withdraw their shares that have been invested. Earnings per share significant effect on firm value due to the higher value earning per share then it will affect the amount of net loss given by the company to shareholders. The size of the company is not able to moderate the relationship between earnings management on firm value because the size of the company is getting bigger, the management will minimize fraud in carrying out earnings management practices because outside supervision is increasing strictly towards internal parties, so that internal parties will increase transparency and truth in information. Company size is able to moderate the relationship between earning per share large companies are supported by good resources and it is easy to meet capital needs, including through foreign capital.